Avaliação dos atributos em dor lombar crônica: descrição e intensidade de dor, qualidade de vida, incapacidade e depressão - Stefane, Thais (2012)
The chronic low back pain can cause a deficit in the quality of life, which commits daily activities, employment, social, leisure and causes emotional damage. This study justified the need for greater knowledge in the perception of chronic low back pain in our context and on its impact on daily life, reinforcing the importance of the measurement and assessment of pain in enabling the treatment effectiveness. This study aims to evaluate patients with chronic low back pain and specific objectives of socio-demographically that characterize these patients, to identify the level of quality of life, the level of disability, the level of depression, the intensity of perceived pain and characterize chronic low back pain through the pain descriptors and associate quality of life and pain intensity, quality of life and depression, depression and intensity of pain, disability and intensity of pain, disability and quality of life, disability and depression. A cross-sectional descriptive study was performed. The convenience sample consisted of patients treated as outpatients in a Pain Clinic of São Carlos, Brazil and everyone had the medical diagnosis of chronic low back pain. The data collection was accomplished by structured interviews using the following instruments: instrument to characterize demographic and socio-economic status of the patient; numeric scale (0-10) to measure the intensity of pain; BDI - Beck Depression Inventory for assess the level of depression; WHOQOL-BREF to assess quality of life, Roland-Morris Questionnaire for disability and the Multidimensional Pain Evaluation Scale (EMADOR) an instrument for descriptors of pain for the characterization of chronic pain. The study included 97 subjects, the pain intensity at the moment of interview was 5,4 (2,9) and the mean quality of life was 48,1 (24,2 ) points. The physical domain of quality of life was the most affected with 44,1 (21) points, the mean of disability was 14,4 (6) and the average score of depression was 15,3 (9,6), with 21,6% of the sample had some level of depression. There was a strong association between the physical domain of quality of life and disability. The associations between depression and pain intensity were considered weak. The associations between depression and quality of life domains showed moderate negative correlations with the physical and psychological domains of quality of life and between depression and disability correlated moderate positively. The descriptors that best describe the pain were classified as sensitive and evaluative. These findings indicate that people with chronic low back pain may possibly have other dimensions affected by pain that not only the physical, and thus, health professionals need to perform a comprehensive assessment of pain perception in order to propose their appropriate management.